2016
DOI: 10.1002/smll.201502167
|View full text |Cite
|
Sign up to set email alerts
|

DNA Nanotechnology for Precise Control over Drug Delivery and Gene Therapy

Abstract: Nanomedicine has been growing exponentially due to its enhanced drug targeting and reduced drug toxicity. It uses the interactions where nanotechnological components and biological systems communicate with each other to facilitate the delivery performance. At this scale, the physiochemical properties of delivery systems strongly affect their capacities. Among current delivery systems, DNA nanotechnology shows many advantages because of its unprecedented engineering abilities. Through molecular recognition, DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 95 publications
(229 reference statements)
0
99
0
Order By: Relevance
“…For a molecular delivery system, the first step that needs to be considered is a method for cellular internalisation. There are multiple ways by which DNA nanostructures are believed to enter the cell, which can involve endocytotic or non‐endocytotic pathways . The endocytotic pathways may include clathrin‐mediated endocytosis, caveloae‐mediated endocytosis, phagocytosis and macropinocytosis.…”
Section: Dna Nanostructure Uptake and Stabilisation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For a molecular delivery system, the first step that needs to be considered is a method for cellular internalisation. There are multiple ways by which DNA nanostructures are believed to enter the cell, which can involve endocytotic or non‐endocytotic pathways . The endocytotic pathways may include clathrin‐mediated endocytosis, caveloae‐mediated endocytosis, phagocytosis and macropinocytosis.…”
Section: Dna Nanostructure Uptake and Stabilisation Strategiesmentioning
confidence: 99%
“…Unsurprisingly, however, it is an attractive choice for use in biological and medical applications, as well. DNA origami as a drug‐delivery vehicle has been receiving much attention recently, and has been extensively assessed in detail by many excellent reviews . For practical use in a biological context, DNA origami structures should interact stably and efficiently with cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Recently, larger and more complex nanomachines have also been designed and made, including DNA nanorobots that are capable of serving as switches, rotors, joints and logic gated carriers. [7][8][9] The success in creating molecular and nanomachines indeed opens up tremendous opportunities of performing unprecedented tasks at the molecular length scale. Nevertheless, we are still a few steps behind the Feynman-type nanorobots, which probably require the combination of nanomachinery parts across various length scales for performing intelligent and sophisticated functions.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomedicines offer notable advantages compared to traditional drug delivery methods including transportation of higher drug payloads, prolonged drug circulation and improved bioavailability, synergistic effects due to simultaneous administration of multiple drugs with different activities, and improved therapeutic indices through enhanced permeability, retention, and programed design . Recent studies showed that single‐stranded DNA nanostructures provide tunable, precise, rationally designed drug delivery vehicles that can be further functionalized with judiciously chosen ligands for cell‐specific and targeted therapy …”
Section: Introductionmentioning
confidence: 99%